Cultivating writers : elevate your writing instruction beyond the skills to ignite the will - Elliott, Anne (Anne Marie); Lynch, Mary, 1962- (Pembroke Publishers, 2020)
"Cultivating Writers introduces educators to 6 essential beliefs to nurture and grow complete writers who have the will to write. Strategies throughout the book show teachers how to create an environment that helps students see writing as a rewarding experience in and outside the classroom. Powerful real-life anecdotes and ready-to-use activities support this guide to developing classrooms full of thoughtful, passionate writers."--